Effect of Weld Parameters on Residual Stress, Hardness and Microstructure of Dissimilar AA2024-T3 and AA7475-T761 Friction Stir Welded Joints - Delijaicov,Sergio (2018)
This study presents the effect of the welding parameters variation on the results of forces, temperature, residual stresses and Vickers micro hardness of dissimilar butt joints of AA2024-T3 and AA7475-T761 welded by friction stir welding (FSW). The tool rotational speed, feed rate and tool tilt angle were investigated using the Design of Experiments method. The obtained results of penetration force, temperature in the weld zone compared with the microscopic analysis of the microstructure showed that it is necessary a minimum amount of force and heat input to obtain a defect free weld zone. It was also notable that, friction stir welding has a wide stability range of its most significant parameters - rotational speed and feed rate - which grantee this minimum condition. Micro hardness’ profiles showed the effect of the grain size refinement towards the thermo-mechanically affected zone as well as, the effect of recrystallization inside the nugget. Residual stresses’ profiles showed a tensile stress peak at the shoulder contact area due the pressure with the base material on thermo-mechanically affected zone and the stress relief effect caused by high temperatures in the nugget resulting in a decrease in residual stress value. The most significant variables for residual stress results were rotational speed of the tool and welding feed rate, once their interaction rule the heat input in the weld zone.